Synchrotron Time-Lapse Imaging of Lignocellulosic Biomass Hydrolysis: Tracking Enzyme Localization by Protein Autofluorescence and Biochemical Modification of Cell Walls by Microfluidic Infrared Microspectroscopy - Devaux, Marie-Françoise; Jamme, Frédéric; André, William; Bouchet, Brigitte; Alvarado, Camille; Durand, Sylvie; Robert, Paul; Saulnier, Luc; Bonnin, Estelle; Guillon, Fabienne (Frontiers in Plant Science, 2018)
Tracking enzyme localization and following the local biochemical modification of the substrate should help explaining the recalcitrance of lignocellulosic plant cell walls to enzymatic degradation. Time-lapse studies using conventional imaging requires enzyme labelling and following the biochemical modifications of biopolymers found in plant cell walls, which cannot be easily achieved revealed. In the present work, synchrotron facilities have been investigated forused to imageing theof enzymatic degradation of lignocellulosic biomass without labelling the enzyme or the cell walls. Multichannel autofluorescence imaging of the protein and phenolic compounds after excitation at 275 nm highlighted the presence or absence of enzymes on cell walls and made it possible toallowed tracking them during the reaction. Image analysis was achieved used to quantify the fluorescence intensity variations. Consistent variations in theof enzyme concentration were found locally for cell cavities and their surrounding cell walls. Microfluidic FT-IR microspectroscopy allowed for time-lapse tracking of local changes in the polysaccharides in cell walls during degradation. Hemicellulose degradation was found to occur prior to cellulose degradation using a Celluclast® preparation. Combining the fluorescence and FT-IR information yieldedlead the following conclusion that: enzymes did not bind to lignified cell walls, which that were consequently not degraded. Fluorescence multiscale imaging and FT-IR microspectroscopy showed an unexpected variability both in the initial biochemical composition and the degradation pattern, highlighting micro-domains in the cell wall of a given cell. Fluorescence intensity quantifications showed that the enzymes were not evenly distributed, and their amount increased progressively on degradable cell walls. During degradation, adjacent cells were separated and the cell wall fragmented until full complete degradation.